A modified polylactic acid copolyester and a highly transparent biodegradable heat shrinkable film
Through the copolymerization technology of polylevollactic acid, flexible polyester and polyractic lactic acid, combined with polyisocyanate chain extender, a high transparency and biodegradable heat shrink film was prepared, which solved the problem of non-degradability and insufficient brittleness of existing heat shrink film materials, and achieved the improvement of the biodegradability and mechanical properties of the material.
Patent Information
- Application Number
- CN202310734942.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-20
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2043-06-20
AI Technical Summary
The existing heat shrink film materials are mainly based on petroleum-based plastics, which have problems of non-degradability and environmental pollution. At the same time, the polylactic acid material itself is insufficiently brittle, which limits its application in the field of heat shrink films.
By using copolymerization technology of polylevollactic acid prepolymer, flexible degradable polyester and polyractic lactic acid prepolymer, modified polylactic acid copolyester is prepared, and combined with polyisocyanate as a chain extender, a high transparency and biodegradable heat shrink film is formed.
It is possible to prepare a heat shrink film with high transparency, biodegradability and excellent mechanical properties without the need for an additional filler additive, and overcome the problem of insufficient brittleness of polylactic acid materials.
Smart Images

Figure CN116731298B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of polymer materials, and in particular to a modified polylactic acid copolyester and a highly transparent biodegradable heat shrinkable film. Background Art
[0002] In recent years, the use of non-degradable plastic bags, disposable plastic tableware, disposable items in hotels, and quick-release plastic packaging has been gradually restricted. As a bio-based degradable polymer material, polylactic acid has attracted much attention from the industry and enterprises. Polylactic acid can be prepared by polycondensation of lactic acid or ring-opening polymerization of lactide, and its raw materials come from bio-based corn, etc. In addition, polylactic acid has good biocompatibility and mechanical properties, and is widely used in injection molding, blow molding, textile and other fields.
[0003] Heat shrink film has the characteristics of high gloss, good wear resistance, and good puncture resistance. It is widely used in food packaging, daily cosmetics and other fields. Its market demand has continued to grow in recent years, and its development potential is huge. At present, the commonly used heat shrink films on the market are mainly based on petroleum-based plastic materials such as polypropylene, polyvinyl chloride and modified polyethylene terephthalate, which come from non-renewable resources and are non-degradable under natural conditions, which can easily cause environmental pollution problems. Therefore, it is urgent to prepare a biodegradable heat shrink film that meets the application requirements. However, due to the defects of polylactic acid itself, such as brittleness, its application in the field of heat shrink film is limited.
[0004] Patent CN112226050A discloses a method for preparing heat shrinkable materials by using polyamide blended modified polylactic acid. The added polyamide is difficult to degrade and has compatibility issues with polylactic acid, which greatly affects the transparency of the film. Patent CN114015185A uses allyl (diisopropylamino) dimethyl silane as an initiator to prepare modified polylactic acid through ring-opening polymerization, but the added allyl (diisopropylamino) dimethyl silane will have a greater negative impact on the environment. Summary of the invention
[0005] In order to solve the technical problem that the existing heat shrinkable film is difficult to degrade, the present invention provides a modified polylactic acid copolyester and a highly transparent biodegradable heat shrinkable film. The modified polylactic acid copolyester of the present invention is particularly suitable for preparing heat shrinkable films, and can be used to prepare biodegradable polylactic acid heat shrinkable films without adding any filler additives. It not only has high transparency and biodegradability, but also overcomes the disadvantage of low brittleness of ordinary polylactic acid itself, so that the film material has both excellent toughness and strength.
[0006] To this end, the specific technical solution of the present invention is:
[0007] A modified polylactic acid copolyester, which is obtained by copolymerizing a poly-L-lactic acid prepolymer component a, a flexible degradable polyester component b and a poly-racemic lactic acid prepolymer component c through a chain extender to form a linear modified polylactic acid copolyester;
[0008] Wherein, the component a is prepared by ring-opening polymerization of L-lactide; the component b is a low molecular weight polyester; the component c is prepared by ring-opening polymerization of meso / racemic lactide; the chain extender is a polyisocyanate;
[0009] The weight ratio of component a, component b and component c is (13.3-40): (10-20): (40-66.7), and the total is 100;
[0010] The number average molecular weight of the modified polylactic acid copolyester is 20000-200000 g / mol;
[0011] The number average molecular weight of the poly-L-lactic acid prepolymer is 500-20000 g / mol;
[0012] The number average molecular weight of the polyracemic lactic acid prepolymer is 500-20000 g / mol;
[0013] The low molecular weight polyester is selected from PBS, PBAT or PCL with a number average molecular weight of 500-20000 g / mol.
[0014] As a further improvement of the present invention, the number average molecular weight of the poly-L-lactic acid prepolymer is 2000-6000 g / mol; the number average molecular weight of the poly-racemic lactic acid prepolymer is 2500-15000 g / mol; and the low molecular weight polyester is PCL with a number average molecular weight of 2500-10000 g / mol.
[0015] More preferably, the weight ratio of component a, component b and component c is 20:20:60;
[0016] The number average molecular weight of the poly-L-lactic acid prepolymer is 2500 g / mol;
[0017] The number average molecular weight of the polyracemic lactic acid prepolymer is 10000 g / mol;
[0018] The number average molecular weight of the PCL is 2500 g / mol. In this case, the synergistic effect of the low molecular weight polyester and other components is better.
[0019] Furthermore, the chain extender is hexamethylene diisocyanate, 4,4'-methylenebis(phenyl isocyanate), meta-xylene diisocyanate or para-phenylene diisocyanate. The preferred amount of the chain extender is 1-3 times the total molar number of the terminal hydroxyl groups of component a and component c. If the amount of the chain extender is too little, part of the prepolymer will not be able to participate in the chain extension reaction, and the low molecular weight polymer will act as a plasticizer in the polymer system, reducing the mechanical properties. If the amount of the chain extender is too high, the polyurethane bond synthesized by the isocyanate group and the hydroxyl (carboxyl) group will act as a hard segment, and too much hard segment content will prevent the material from forming a good microphase separation structure.
[0020] The modified polylactic acid copolyester of the present invention can be used to prepare a highly transparent biodegradable heat shrinkable film, and the preparation method comprises the following steps:
[0021] (1) Add poly (L-lactic acid) prepolymer component a, flexible degradable polyester component b, and poly (racemic) lactic acid prepolymer component c into a reactor, heat until completely melted, add a chain extender, heat and stir to react under an inert gas atmosphere, cool, dissolve the mixture with chloroform, and precipitate in anhydrous methanol. The resulting precipitate is the modified polylactic acid copolyester. The reaction temperature is preferably 180-220°C, and the stirring reaction time is preferably 150-250 min.
[0022] (2) The dried modified polylactic acid copolyester is melt-extruded in a twin-screw extruder, die-casted, biaxially stretched, and cooled to form a highly transparent biodegradable heat shrinkable film. The melting temperature is preferably 160-200°C, the stretching temperature is preferably 60-100°C, the MD stretching ratio is preferably 2-6 times, and the TD stretching ratio is preferably 2-6 times.
[0023] Conventional polylactic acid (PLA) has poor toughness, and its impact strength and elongation at break are lower than those of commonly used resins. From the structure of PLA, it can be seen that the carbonyl group in the PLA molecular chain is coplanar with the adjacent oxygen atom, and is very close to the adjacent carbon atom, making it difficult to rotate. Therefore, the molecular chain has poor flexibility, and the material is hard and brittle, has poor impact resistance, and has poor film-forming properties. In addition, PLA is easily degraded under the action of acid, alkali, alcohol and water when it is melted, and has poor heat resistance. Therefore, there are many technical problems in the application of conventional PLA as a heat shrink film, and it is difficult to obtain a heat shrink film with ideal functions.
[0024] The ratio and segment length of the components ac of the present invention are crucial to regulating the crystallization and good microphase separation structure of the final modified polylactic acid copolymer. In order to achieve the technical effect claimed in the present invention, the weight ratio of the components ac and the length of their respective segments need to be strictly controlled within the above range to reach a balance point, so that the material has both excellent toughness and strength, and is suitable for preparing heat shrinkable films. Specifically:
[0025] For component a poly-L-lactic acid prepolymer, within the above range, as the content or number average molecular weight of poly-L-lactic acid increases, the strength of the heat shrink film increases. Increased toughness will lead to decreased strength, and a corresponding increase in strength will lead to decreased toughness. Therefore, if the content or molecular weight of the poly-L-lactic acid prepolymer is too small, the strength of the polymer as a whole will be reduced. If it is too high, the toughness of the material will be poor, and the difficulty of the chain extension reaction will also be increased. Therefore, there is a threshold value for the change in content or molecular weight. Regulating the content or molecular weight within the above threshold range can obtain toughness and strength that are more suitable for application.
[0026] For component b polyracemic lactic acid prepolymer, the molecular weight of the chain segment of the low molecular weight polyester should not be too high or too low. If the molecular weight is too high, the end group will be buried by the molecular chain, making it impossible for the end group and isocyanate to approach each other, resulting in no reaction; if the molecular weight is too low, although the reaction rate will be greatly improved, the mechanical properties of the polymer will be seriously affected due to the short molecular chain segment, and a good microphase separation structure cannot be formed.
[0027] For component c, poly(racemic) lactic acid prepolymer, if controlled within the above range, as the content or number average molecular weight of poly(racemic) lactic acid prepolymer increases, the toughness of the heat shrink film increases. Poly(racemic) lactic acid prepolymer itself is a random copolymer, the film is more transparent, and the toughness of the polymer is increased. At the same time, it will reduce the crystallization ability of poly(L-lactic acid), so that the material forms a good microphase separation structure. If the content or molecular weight is too high, the strength of the material will be seriously reduced and cannot meet the use requirements. The best effect is achieved when controlled within the above threshold range.
[0028] The present invention introduces a flexible segment composed of a low molecular weight polyester into the PLA molecular chain, which can improve the flexibility, impact strength, elongation at break, etc. of PLA; adding an amorphous poly racemic lactic acid prepolymer can effectively inhibit the crystallization performance of PLA, so as to obtain a toughened PLA with a longer molecular chain and better flexibility. The present invention regulates the competition between the crystallization and phase separation of the polylactic acid material through the chemical bonding between the three copolymer components a, component b and component c, so that it has an excellent synergistic effect, can solve the technical barriers of polylactic acid in the field of heat shrinkable film, and obtain a biodegradable heat shrinkable film with ideal performance. On this basis, polyisocyanate is used as a chain extender to introduce a polyurethane group to improve the hydrolysis resistance of the material. The present invention can overcome the inherent defect of poor toughness of polylactic acid materials, adopt the copolymer components of poly-L-lactic acid, flexible degradable polyester and polyracemic lactic acid to obtain a modified polylactic acid copolyester, regulate the crystallization and phase structure of the material through the ratio of the three components and the length of the segment, and can prepare a biodegradable polylactic acid heat shrinkable film that meets the use requirements without adding any filler additives.
[0029] Compared with the prior art, the beneficial effects of the present invention are:
[0030] (1) The present invention improves the original performance defects of polylactic acid through targeted chemical structure design, obtains a modified polylactic acid copolymer with excellent performance, realizes the preparation of polylactic acid-based heat shrinkable film, expands the application field of polylactic acid, and the heat shrinkage rate of the prepared heat shrinkable film after stretching is greater than 90%.
[0031] (2) The present invention can directly prepare a transparent biodegradable polylactic acid heat shrinkable film without adding any filler additives by introducing flexible biodegradable polyester and poly(lactic acid). By regulating the crystallization and microphase separation structure through the ratio between components and the molecular weight of each chain segment, a heat shrinkable film with high heat shrinkage performance and puncture resistance can be obtained.
[0032] (3) The present invention uses polylactic acid, polyracemic lactic acid, and polyester raw materials as processing raw materials to produce a green and environmentally friendly heat shrinkable film, which can be degraded into carbon dioxide and water in the natural environment, thereby alleviating the environmental pollution problem caused by the disposal of conventional heat shrinkable films. It is an environmentally friendly material. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Figure 1 The WAXD (a) curves of some example products are shown in FIG.
[0034] Figure 2 The SAXS (b) curves of some example products. DETAILED DESCRIPTION
[0035] The technical solution of the present invention will be clearly and completely described below in conjunction with specific embodiments. Obviously, the described implementation scheme is only a part of the implementation scheme of the present invention, rather than all the implementation schemes. This implementation scheme is implemented on the premise of the technical solution of the present invention, and a detailed implementation method and a specific operation process are given, but the protection scope of the present invention is not limited to the following implementation schemes. All other implementation schemes obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention. Example 1
[0036] A modified polylactic acid copolyester for a biodegradable heat shrinkable film with high transparency is prepared from the following raw materials: based on the total weight of component a, component b and component c, the content of the poly-L-lactic acid prepolymer a is 40wt%, and the number average molecular weight is M n =6.0kg / mol; the content of the flexible degradable polyester PCL is 20wt%, and its number average molecular weight M n =5.0kg / mol; the content of the poly racemic lactic acid prepolymer c is 40wt%, and its number average molecular weight M n=10.0kg / mol; the chain extender is hexamethylene diisocyanate, and its content is 1 times the molar number of terminal hydroxyl groups of the prepolymer.
[0037] In this embodiment, the steps of preparing the highly transparent biodegradable heat shrinkable film are as follows:
[0038] 1) Weigh poly (L-lactic acid) prepolymer a, flexible degradable polyester PCL, poly (racemic) lactic acid prepolymer c and hexamethylene diisocyanate, add poly (L-lactic acid) prepolymer a, flexible degradable polyester PCL and poly (racemic) lactic acid prepolymer c into a reactor, heat until completely melted, add hexamethylene diisocyanate, raise the temperature to 200°C under a nitrogen atmosphere, stir for 180 minutes, cool, dissolve the mixture with chloroform, and precipitate in anhydrous methanol. The precipitate obtained is a modified poly (lactic acid) copolyester with a number average molecular weight of M n =25.9kg / mol.
[0039] 2) Add the obtained modified polylactic acid copolyester into a twin-screw extruder for extrusion, dry the material after granulation, and cast it: the temperature of melt casting is 190°C, and the temperature of the outlet is 180°C; obtain a polylactic acid casting sheet. Put the obtained polylactic acid casting sheet into the stretching fixture of the biaxial stretching equipment, preheat and perform biaxial stretching; the conditions include: preheating temperature of 80°C, stretching temperature of 80°C, MD stretching ratio of 2 times, TD stretching ratio of 2 times; finally, a highly transparent biodegradable heat shrinkable film is prepared. Example 2
[0040] A modified polylactic acid copolyester for a biodegradable heat shrinkable film with high transparency is prepared from the following raw materials: based on the total weight of component a, component b and component c, the content of the poly-L-lactic acid prepolymer a is 20wt%, and the number average molecular weight is M n =6.0kg / mol; the content of the flexible degradable polyester PBS is 20wt%, M n =4.8kg / mol; the content of the poly racemic lactic acid prepolymer c is 60wt%, and its number average molecular weight M n =10.0kg / mol; the chain extender is hexamethylene diisocyanate, and its content is 1 times the molar number of terminal hydroxyl groups in the prepolymer.
[0041] In this embodiment, the steps of preparing the highly transparent biodegradable heat shrinkable film are as follows:
[0042] 1) Weigh poly (L-lactic acid) prepolymer a, flexible degradable polyester PBS, poly (racemic) lactic acid prepolymer c and hexamethylene diisocyanate, add poly (L-lactic acid) prepolymer a, flexible degradable polyester PBS and poly (racemic) lactic acid prepolymer c into a reactor, heat until completely melted, add hexamethylene diisocyanate, raise the temperature to 200°C under a nitrogen atmosphere, stir for 180 minutes, cool, dissolve the mixture with chloroform, and precipitate in anhydrous methanol. The precipitate obtained is a modified poly (lactic acid) copolyester with a number average molecular weight of M n =33.1kg / mol.
[0043] 2) Add the obtained modified polylactic acid copolyester into a twin-screw extruder for extrusion, dry the material after granulation, and cast it: the temperature of melt casting is 190°C, and the temperature of the outlet is 180°C; obtain a polylactic acid casting sheet. Put the obtained polylactic acid casting sheet into the stretching fixture of the biaxial stretching equipment, preheat and perform biaxial stretching; the conditions include: preheating temperature of 80°C, stretching temperature of 80°C, MD stretching ratio of 2 times, TD stretching ratio of 2 times; finally, a highly transparent biodegradable heat shrinkable film is prepared. Example 3
[0044] A modified polylactic acid copolyester for a biodegradable heat shrinkable film with high transparency is prepared from the following raw materials: based on the total weight of component a, component b and component c, the content of the poly-L-lactic acid prepolymer a is 20wt%, and the number average molecular weight is M n =6.0kg / mol; the content of the flexible biodegradable polyester PBAT is 20wt%, M n =4.2kg / mol; the content of the poly racemic lactic acid prepolymer c is 60wt%, and its number average molecular weight M n =10.0kg / mol; the chain extender is hexamethylene diisocyanate, and its content is 1 times the molar number of terminal hydroxyl groups of the prepolymer.
[0045] In this embodiment, the steps of preparing the highly transparent biodegradable heat shrinkable film are as follows:
[0046] 1) Weigh poly (L-lactic acid) prepolymer a, flexible biodegradable polyester PBAT, poly (racemic) lactic acid prepolymer c and hexamethylene diisocyanate, add poly (L-lactic acid) prepolymer a, flexible biodegradable polyester PBAT and poly (racemic) lactic acid prepolymer c into a reactor, heat until completely melted and then add hexamethylene diisocyanate, raise the temperature to 200°C under a nitrogen atmosphere, stir for 180 minutes, cool, dissolve the mixture with chloroform, and precipitate in anhydrous methanol. The precipitate obtained is a modified poly (lactic acid) copolyester with a number average molecular weight of Mn =32.7kg / mol.
[0047] 2) Add the obtained modified polylactic acid copolyester into a twin-screw extruder for extrusion, dry the material after granulation, and cast it: the temperature of melt casting is 190°C, and the temperature of the outlet is 180°C; obtain a polylactic acid casting sheet. Put the obtained polylactic acid casting sheet into the stretching fixture of the biaxial stretching equipment, preheat and perform biaxial stretching; the conditions include: preheating temperature of 80°C, stretching temperature of 100°C, MD stretching ratio of 2 times, TD stretching ratio of 2 times; finally, a highly transparent biodegradable heat shrinkable film is prepared. Example 4
[0048] A modified polylactic acid copolyester for a biodegradable heat shrinkable film with high transparency is prepared from the following raw materials: based on the total weight of component a, component b and component c, the content of the poly-L-lactic acid prepolymer a is 20wt%, and the number average molecular weight is M n =6.0kg / mol; the content of the flexible degradable polyester PCL is 20wt%, and its number average molecular weight M n =5.0kg / mol; the content of the poly racemic lactic acid prepolymer c is 60wt%, and its number average molecular weight M n =10.0kg / mol; the chain extender is hexamethylene diisocyanate, and its content is 1 times the molar number of terminal hydroxyl groups of the prepolymer.
[0049] In this embodiment, the steps of preparing the highly transparent biodegradable heat shrinkable film are as follows:
[0050] 1) Weigh poly (L-lactic acid) prepolymer a, flexible degradable polyester PCL, poly (racemic) lactic acid prepolymer c and hexamethylene diisocyanate, add poly (L-lactic acid) prepolymer a, flexible degradable polyester PCL and poly (racemic) lactic acid prepolymer c into a reactor, heat until completely melted, add hexamethylene diisocyanate, raise the temperature to 200°C under a nitrogen atmosphere, stir for 180 minutes, cool, dissolve the mixture with chloroform, and precipitate in anhydrous methanol. The precipitate obtained is a modified poly (lactic acid) copolyester with a number average molecular weight of M n =35.7kg / mol.
[0051] 2) Add the obtained modified polylactic acid copolyester into a twin-screw extruder for extrusion, dry the material after granulation, and cast it: the temperature of melt casting is 190°C, and the temperature of the outlet is 180°C; obtain a polylactic acid casting sheet. Put the obtained polylactic acid casting sheet into the stretching fixture of the biaxial stretching equipment, preheat and perform biaxial stretching; the conditions include: preheating temperature of 80°C, stretching temperature of 90°C, MD stretching ratio of 3 times, TD stretching ratio of 3 times; finally, a highly transparent biodegradable heat shrinkable film is prepared. Example 5
[0052] A modified polylactic acid copolyester for a biodegradable heat shrinkable film with high transparency is prepared from the following raw materials: based on the total weight of component a, component b and component c, the content of the poly-L-lactic acid prepolymer a is 13.3wt%, and the number average molecular weight is M n =6.0kg / mol; the content of the flexible degradable polyester PCL is 20wt%, and its number average molecular weight M n =5.0kg / mol; the content of the poly racemic lactic acid prepolymer c is 66.7wt%, and its number average molecular weight M n =10.0kg / mol; the chain extender is hexamethylene diisocyanate, and its content is twice the molar number of terminal hydroxyl groups of the prepolymer.
[0053] In this embodiment, the steps of preparing the highly transparent biodegradable heat shrinkable film are as follows:
[0054] 1) Weigh poly (L-lactic acid) prepolymer a, flexible degradable polyester PCL, poly (racemic) lactic acid prepolymer c and hexamethylene diisocyanate, add poly (L-lactic acid) prepolymer a, flexible degradable polyester PCL and poly (racemic) lactic acid prepolymer c into a reactor, heat until completely melted, add hexamethylene diisocyanate, raise the temperature to 200°C under a nitrogen atmosphere, stir for 180 minutes, cool, dissolve the mixture with chloroform, and precipitate in anhydrous methanol. The precipitate obtained is a modified poly (lactic acid) copolyester with a number average molecular weight of M n =37.1kg / mol.
[0055] 2) Add the obtained modified polylactic acid copolyester into a twin-screw extruder for extrusion, dry the material after granulation, and cast it: the temperature of melt casting is 190°C, and the temperature of the outlet is 180°C; obtain a polylactic acid casting sheet. Put the obtained polylactic acid casting sheet into the stretching fixture of the biaxial stretching equipment, preheat and perform biaxial stretching; the conditions include: preheating temperature of 80°C, stretching temperature of 90°C, MD stretching ratio of 3 times, TD stretching ratio of 5 times; finally, a highly transparent biodegradable heat shrinkable film is prepared. Example 6
[0056] A modified polylactic acid copolyester for a biodegradable heat shrinkable film with high transparency is prepared from the following raw materials: based on the total weight of component a, component b and component c, the content of the poly-L-lactic acid prepolymer a is 20wt%, and the number average molecular weight is M n =2.5kg / mol; the content of the flexible degradable polyester PCL is 20wt%, and its number average molecular weight M n = 2.5kg / mol; the content of the poly racemic lactic acid prepolymer c is 60wt%, and its number average molecular weight M n =10.0kg / mol; the chain extender is hexamethylene diisocyanate, and its content is 1 times the molar number of terminal hydroxyl groups of the prepolymer.
[0057] In this embodiment, the steps of preparing the highly transparent biodegradable heat shrinkable film are as follows:
[0058] 1) Weigh poly (L-lactic acid) prepolymer a, flexible degradable polyester PCL, poly (racemic) lactic acid prepolymer c and hexamethylene diisocyanate, add poly (L-lactic acid) prepolymer a, flexible degradable polyester PCL and poly (racemic) lactic acid prepolymer c into a reactor, heat until completely melted, add hexamethylene diisocyanate, raise the temperature to 200°C under a nitrogen atmosphere, stir for 180 minutes, cool, dissolve the mixture with chloroform, and precipitate in anhydrous methanol. The precipitate obtained is a modified poly (lactic acid) copolyester with a number average molecular weight of M n =23.8kg / mol.
[0059] 2) Add the obtained modified polylactic acid copolyester into a twin-screw extruder for extrusion, dry the material after granulation, and cast it: the temperature of melt casting is 190°C, and the temperature of the outlet is 180°C; obtain a polylactic acid casting sheet. Put the obtained polylactic acid casting sheet into the stretching fixture of the biaxial stretching equipment, preheat and perform biaxial stretching; the conditions include: preheating temperature of 80°C, stretching temperature of 90°C, MD stretching ratio of 4 times, TD stretching ratio of 4 times; finally, a highly transparent biodegradable heat shrinkable film is prepared. Example 7
[0060] A modified polylactic acid copolyester for a biodegradable heat shrinkable film with high transparency is prepared from the following raw materials: based on the total weight of component a, component b and component c, the content of poly (L-lactic acid) prepolymer a is 30wt%, and the number average molecular weight is M n =6.0kg / mol; the content of the flexible degradable polyester PCL is 10wt%, and its number average molecular weight Mn =5.0kg / mol; the content of the poly racemic lactic acid prepolymer c is 60wt%, and its number average molecular weight M n =10.0kg / mol; the chain extender is hexamethylene diisocyanate, and its content is 3 times the molar number of terminal hydroxyl groups of the prepolymer.
[0061] In this embodiment, the steps of preparing the highly transparent biodegradable heat shrinkable film are as follows:
[0062] 1) Weigh poly (L-lactic acid) prepolymer a, flexible degradable polyester PCL, poly (racemic) lactic acid prepolymer c and hexamethylene diisocyanate, add poly (L-lactic acid) prepolymer a, flexible degradable polyester PCL and poly (racemic) lactic acid prepolymer c into a reactor, heat until completely melted, add hexamethylene diisocyanate, raise the temperature to 200°C under a nitrogen atmosphere, stir for 180 minutes, cool, dissolve the mixture with chloroform, and precipitate in anhydrous methanol. The precipitate obtained is a modified poly (lactic acid) copolyester with a number average molecular weight of M n =32.5kg / mol.
[0063] 2) Add the obtained modified polylactic acid copolyester into a twin-screw extruder for extrusion, dry the material after granulation, and cast it: the temperature of melt casting is 190°C, and the temperature of the outlet is 180°C; obtain a polylactic acid casting sheet. Put the obtained polylactic acid casting sheet into the stretching fixture of the biaxial stretching equipment, preheat and perform biaxial stretching; the conditions include: preheating temperature of 80°C, stretching temperature of 100°C, MD stretching ratio of 6 times, TD stretching ratio of 6 times; finally, a highly transparent biodegradable heat shrinkable film is prepared. Example 8
[0064] A modified polylactic acid copolyester for a biodegradable heat shrinkable film with high transparency is prepared from the following raw materials: based on the total weight of component a, component b and component c, the content of the poly-L-lactic acid prepolymer a is 25wt%, and the number average molecular weight is M n =20.0kg / mol; the content of the flexible degradable polyester PCL is 15wt%, and its number average molecular weight M n = 20.0kg / mol; the content of the poly racemic lactic acid prepolymer c is 60wt%, and its number average molecular weight M n =20.0kg / mol; the chain extender is hexamethylene diisocyanate, and its content is 1 times the molar number of terminal hydroxyl groups of the prepolymer.
[0065] In this embodiment, the steps of preparing the highly transparent biodegradable heat shrinkable film are as follows:
[0066] 1) Weigh poly (L-lactic acid) prepolymer a, flexible degradable polyester PCL, poly (racemic) lactic acid prepolymer c and hexamethylene diisocyanate, add poly (L-lactic acid) prepolymer a, flexible degradable polyester PCL and poly (racemic) lactic acid prepolymer c into a reactor, heat until completely melted, add hexamethylene diisocyanate, raise the temperature to 200°C under a nitrogen atmosphere, stir for 180 minutes, cool, dissolve the mixture with chloroform, and precipitate in anhydrous methanol. The precipitate obtained is a modified poly (lactic acid) copolyester with a number average molecular weight of M n =198.2kg / mol.
[0067] 2) Add the obtained modified polylactic acid copolyester into a twin-screw extruder for extrusion, dry the material after granulation, and cast it: the temperature of melt casting is 190°C, and the temperature of the outlet is 180°C; obtain a polylactic acid casting sheet. Put the obtained polylactic acid casting sheet into the stretching fixture of the biaxial stretching equipment, preheat and perform biaxial stretching; the conditions include: preheating temperature of 80°C, stretching temperature of 80°C, MD stretching ratio of 2 times, TD stretching ratio of 2 times; finally, a highly transparent biodegradable heat shrinkable film is prepared. Example 9
[0068] A modified polylactic acid copolyester for a biodegradable heat shrinkable film with high transparency is prepared from the following raw materials: based on the total weight of component a, component b and component c, the content of the poly-L-lactic acid prepolymer a is 30wt%, and the number average molecular weight is M n =0.5kg / mol; the content of the flexible degradable polyester PCL is 15wt%, and its number average molecular weight M n =0.5kg / mol; the content of the poly racemic lactic acid prepolymer c is 55wt%, and its number average molecular weight M n =0.5kg / mol; the chain extender is hexamethylene diisocyanate, and its content is 1 times the molar number of terminal hydroxyl groups of the prepolymer.
[0069] In this embodiment, the steps of preparing the highly transparent biodegradable heat shrinkable film are as follows:
[0070] 1) Weigh poly (L-lactic acid) prepolymer a, flexible degradable polyester PCL, poly (racemic) lactic acid prepolymer c and hexamethylene diisocyanate, add poly (L-lactic acid) prepolymer a, flexible degradable polyester PCL and poly (racemic) lactic acid prepolymer c into a reactor, heat until completely melted, add hexamethylene diisocyanate, raise the temperature to 200°C under a nitrogen atmosphere, stir for 180 minutes, cool, dissolve the mixture with chloroform, and precipitate in anhydrous methanol. The precipitate obtained is a modified poly (lactic acid) copolyester with a number average molecular weight of M n =20.4kg / mol.
[0071] 2) Add the obtained modified polylactic acid copolyester into a twin-screw extruder for extrusion, dry the material after granulation, and cast it: the temperature of melt casting is 190°C, and the temperature of the outlet is 180°C; obtain a polylactic acid casting sheet. Put the obtained polylactic acid casting sheet into the stretching fixture of the biaxial stretching equipment, preheat and perform biaxial stretching; the conditions include: preheating temperature of 80°C, stretching temperature of 80°C, MD stretching ratio of 2 times, TD stretching ratio of 2 times; finally, a highly transparent biodegradable heat shrinkable film is prepared.
[0072] Comparative Example 1
[0073] A modified polylactic acid for a biodegradable heat shrinkable film is prepared from the following raw materials: based on the weight of the modified polylactic acid copolyester, the content of the poly-L-lactic acid prepolymer a is 100wt%, and the number average molecular weight thereof is
[0074] In this comparative example, the steps of the preparation method of the biodegradable heat shrinkable film are as follows:
[0075] 1) Weigh poly (L-lactic acid) prepolymer a and hexamethylene diisocyanate, add poly (L-lactic acid) prepolymer a into a reactor, heat until completely melted, then add hexamethylene diisocyanate, raise the temperature to 200°C under a nitrogen atmosphere, stir for 180 minutes, cool, dissolve the mixture with chloroform, and precipitate in anhydrous methanol. The resulting precipitate is the modified polylactic acid.
[0076] 2) Add the obtained modified polylactic acid copolyester into a twin-screw extruder for extrusion, dry the material after granulation, and cast it: the temperature of melt casting is 190°C, and the temperature of the outlet is 180°C; obtain a polylactic acid cast sheet. Put the obtained polylactic acid cast sheet into the stretching fixture of the biaxial stretching equipment, preheat and perform biaxial stretching; the conditions include: the preheating temperature is 80°C, the stretching temperature is 80°C, the moldability is poor, and no heat shrinkable film can be obtained.
[0077] Comparative Example 2
[0078] A modified polylactic acid copolyester for biodegradable heat shrinkable film is prepared from the following raw materials: based on the weight of the modified polylactic acid copolyester, the content of the poly-L-lactic acid prepolymer a is 60wt%, and the number average molecular weight is
[0079] In this comparative example, the steps of the preparation method of the biodegradable heat shrinkable film are as follows:
[0080] 1) Weigh poly (L-lactic acid) prepolymer a, flexible biodegradable polyester PCL and hexamethylene diisocyanate, add poly (L-lactic acid) prepolymer a and flexible biodegradable polyester PCL into a reactor, heat until completely melted, add hexamethylene diisocyanate, raise the temperature to 200 °C under a nitrogen atmosphere, stir for 180 min, cool, dissolve the mixture with chloroform, and precipitate in anhydrous methanol. The resulting precipitate is the modified polylactic acid copolyester.
[0081] 2) Add the obtained modified polylactic acid copolyester into a twin-screw extruder for extrusion, dry the material after granulation, and cast it: the temperature of melt casting is 190°C, and the temperature of the outlet is 180°C; obtain a polylactic acid casting sheet. Put the obtained polylactic acid casting sheet into the stretching fixture of the biaxial stretching equipment, preheat and perform biaxial stretching; the conditions include: preheating temperature of 80°C, stretching temperature of 100°C, MD stretching ratio of 2 times, TD stretching ratio of 1 times; finally prepare a heat shrinkable film.
[0082] Performance Test:
[0083] (1) Thermal shrinkage test: The film was cut into squares of 5 cm × 5 cm and immersed in hot water at 98 ± 0.5 °C for 10 seconds without a load for thermal shrinkage. The sample was then immersed in water at 25 °C ± 0.5 °C for 10 seconds. After the sample was removed from the water, the longitudinal and transverse dimensions of the film were measured and the thermal shrinkage was calculated according to the following formula.
[0084] Thermal shrinkage ratio (%) = {(length before shrinkage - length after shrinkage) / length before shrinkage} × 100
[0085] (2) Biodegradability test: The test method is as follows: stir soil and distilled water at a mass ratio of 1:10 for 1 hour, centrifuge and filter to obtain the supernatant for use. Put the accurately weighed degradable film (40mm*100mm) into the supernatant, take out the degradable sample after a period of time, wash, dry and weigh. Degradation performance calculation formula: mass loss rate = (mass before degradation - mass after degradation) / mass before degradation. The experimental results show that the 180-day mass loss rate of the transparent polylactic acid film of Examples 1 to 6 is basically higher than 30%, and has excellent degradation performance.
[0086] Table 1: Key differences between Examples 1-7 and Comparative Examples 1-2
[0087]
[0088] Table 2: Molecular weight of modified polylactic acid copolyester and its heat shrink film performance test results
[0089]
[0090] In the prepared materials, the crystallization of poly-L-lactic acid prepolymer (PLLA) and the microphase separation between PLA / polyester are in a competitive relationship. Therefore, it is necessary to regulate the proportion of each component and the length of the chain segment to regulate the crystallization behavior and phase structure.
[0091] When the content of poly(d-lactic acid) (PDLLA) is high, the amorphous PDLLA will inhibit the crystallization of PLLA. Figure 1 , 2 As shown in the figure, it can be seen from Example 1 and Example 4 that when the ratio of PLLA to PDLLA is 1:1 and 1:3, PLLA has an obvious crystallization peak, corresponding to the homogeneous crystallization of PLLA. At this time, polylactic acid crystallization dominates the competition, resulting in no obvious diffraction peak in the SAXS curve. The high crystallinity leads to a material elongation at break of less than 5%.
[0092] In Example 5, due to the further increase in the proportion of PDLLA, the crystallization of polylactic acid is inhibited, and the driving force for crystallization is reduced. The microphase separation caused by the polarity difference between polymers produces nano-domains of about 50 nm, and these structures play a role of nano-enhancement. Therefore, even if the proportion of PDLLA reaches more than 60%, the elongation at break is increased by about 70 times compared with 1:1 in Example 1, and the material strength is still 1 / 2 of that in Example 1.
[0093] In Example 7, crystallization and microphase separation are carried out simultaneously, so that the material maintains the highest strength while showing good ductility, and the elongation at break reaches 500% or more. Therefore, by regulating the molecular weight and ratio of amorphous and crystalline polylactic acid segments, regulating the crystallization and phase separation structure, a polylactic acid film material with excellent performance can be obtained.
[0094] Compared with Example 4, Examples 2 and 3 have better strength and poorer toughness. However, in Examples 2 and 3, since the prepolymers PBS and PBAT are prepared by polycondensation, the molecular weight distribution of the material obtained by chain extension at the same PLLA / PDLLA reaction ratio is wide, which is not conducive to obtaining a good microphase separation structure.
[0095] In comparative example 1, PLLA is used as the main polymer, and the moldability is poor. In comparative example 2, the amorphous PDLLA component is missing, and PLLA crystallization is dominant, resulting in poor toughness of the material.
[0096] The invention can prepare a biodegradable polylactic acid heat shrinkable film without adding any filler additives, and not only has high transparency and biodegradability, but also overcomes the disadvantage of low brittleness of common polylactic acid itself, and significantly improves the toughness and strength of the film material.
[0097] The present invention is not limited to the above-mentioned embodiments. On the basis of the technical solution disclosed in the present invention, technicians in this field can make some substitutions and deformations to some technical features therein according to the disclosed technical content without creative labor, and these substitutions and deformations are all within the protection scope of the present invention.
Claims
1. A modified polylactic acid copolyester, characterized in that: A linear modified polylactic acid copolyester is formed by copolymerizing a poly-L-lactic acid prepolymer component a, a flexible degradable polyester component b and a poly-racemic lactic acid prepolymer component c through a chain extender; Wherein, the component a is prepared by ring-opening polymerization of L-lactide; the component b is a low molecular weight polyester; the component c is prepared by ring-opening polymerization of meso / racemic lactide; the chain extender is a polyisocyanate; The weight ratio of component a, component b and component c is (13.3-30): (10-20): (60-66.7), and the total is 100; The number average molecular weight of the modified polylactic acid copolyester is 23800-198200 g / mol; The number average molecular weight of the poly-L-lactic acid prepolymer is 2500-20000 g / mol; The number average molecular weight of the polyracemic lactic acid prepolymer is 10000-20000 g / mol; The low molecular weight polyester is PCL with a number average molecular weight of 2500-20000 g / mol.
2. The modified polylactic acid copolyester according to claim 1, characterized in that: The weight ratio of component a, component b and component c is 20:20:60; The number average molecular weight of the poly-L-lactic acid prepolymer is 2500 g / mol; The number average molecular weight of the polyracemic lactic acid prepolymer is 10000 g / mol; The number average molecular weight of the PCL is 2500 g / mol.
3. The modified polylactic acid copolyester according to claim 1 or 2, characterized in that: The chain extender is hexamethylene diisocyanate, 4,4'-methylenebis(phenyl isocyanate), meta-xylylene diisocyanate or para-phenylene diisocyanate.
4. The modified polylactic acid copolyester according to claim 3, characterized in that: The amount of the chain extender used is 1-3 times the total molar number of the terminal hydroxyl groups of component a and component c.
5. A highly transparent biodegradable heat shrinkable film, characterized in that: The modified polylactic acid copolyester is prepared according to claim 1, and the preparation method comprises the following steps: (1) adding poly (L-lactic acid) prepolymer component a, flexible degradable polyester component b, and poly (racemic) lactic acid prepolymer component c into a reactor, heating until completely melted, adding a chain extender, heating and stirring to react under an inert gas atmosphere, cooling, dissolving the mixture with chloroform, and precipitating in anhydrous methanol, wherein the obtained precipitate is the modified poly (lactic acid) copolyester; (2) The dried modified polylactic acid copolyester is melt-extruded in a twin-screw extruder, die-casted, biaxially stretched, and cooled to obtain a highly transparent biodegradable heat shrinkable film.
6. The highly transparent biodegradable heat shrinkable film according to claim 5, characterized in that: In step (1), the reaction temperature is 180-220°C, and the reaction is stirred for 150-250 minutes.
7. The highly transparent biodegradable heat shrinkable film according to claim 5, characterized in that: In step (2), the melting temperature is 160-200°C, the stretching temperature is 60-100°C, the MD stretching ratio is 2-6 times, and the TD stretching ratio is 2-6 times.
Citation Information
Patent Citations
Biodegradable heat shrinkable film with high transparency as well as preparation method and application of biodegradable heat shrinkable film
CN112226050A
Biodegradable heat shrink film and processing technology thereof
CN114015185A
Polylactic-acid block copolymer and its preparing method
CN101024696A
Polylactic acid block copolymer, production thereof and molded article made therefrom
JP1997040761A
Cited By
Degradable PBAT modified material and preparation method and application thereof
CN120504942A
Polylactic acid shrink film and preparation method thereof
CN122143454A
Preparation system for polylactic acid shrink film
CN224348341U